CD8 T cells protect adult naive mice from JEV-induced morbidity via lytic function. - Nidhi Jain; Neelam Oswal; Amanpreet Singh Chawla; Tanvi Agrawal; Moanaro Biswas; Sudhanshu Vrati; Satyajit Rath; Anna George; Vineeta Bal; Guruprasad R Medigeshi (Public Library of Science (PLoS), 2017)
Following Japanese encephalitis virus (JEV) infection neutralizing antibodies are shown to provide protection in a significant proportion of cases, but not all, suggesting additional components of immune system might also contribute to elicit protective immune response. Here we have characterized the role of T cells in offering protection in adult mice infected with JEV. Mice lacking α/β-T cells (TCRβ-null) are highly susceptible and die over 10-18 day period as compared to the wild-type (WT) mice which are resistant. This is associated with high viral load, higher mRNA levels of proinflammatory cytokines and breach in the blood-brain-barrier (BBB). Infected WT mice do not show a breach in BBB; however, in contrast to TCRβ-null, they show the presence of T cells in the brain. Using adoptive transfer of cells with specific genetic deficiencies we see that neither the presence of CD4 T cells nor cytokines such as IL-4, IL-10 or interferon-gamma have any significant role in offering protection from primary infection. In contrast, we show that CD8 T cell deficiency is more critical as absence of CD8 T cells alone increases mortality in mice infected with JEV. Further, transfer of T cells from beige mice with defects in granular lytic function into TCRβ-null mice shows poor protection implicating granule-mediated target cell lysis as an essential component for survival. In addition, for the first time we report that γ/δ-T cells also make significant contribution to confer protection from JEV infection. Our data show that effector CD8 T cells play a protective role during primary infection possibly by preventing the breach in BBB and neuronal damage.